Analysis Of Village Institutions’ Performance In Public Services In Sinarancang Village, Mundu Subdistrict - Widia Silviyati; Siti Khumayah; Yanto Heryanto (ann4publisher@gmail.com, 2026)
The performamace of village officials plays a crucial role in determining the quality of public services. Howerver, service delivery in Sinarancang Village still face various obstacles, such as the lack of Srandard Operating Prosedures (SOPs), suboptimal utilization of information tehnology, and inconsistent discipline among officials. This study aims to analyze the performance of Sinarancang Village officials in providing public services and identify the factors that influence them. The study used a descriptive qualitative approach with data collection techniques through interviews, abservation, and docymentation of eight purposively selected informants. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana. The performance of village officials based on indicators of productivity, service quality, responsiveness, and accountability is quite good, but not optimal. The main obstacles include the absence of SOPs, inffective division of tasks, dependence on certain officials, limited information data constraints. Public service problems are interrelated and indicate that service governance is not yet integrated. This study emphasizes the importance of strengthening service governance through the development of standard operating procedures (SOPs), increasing discipline and digital capacity of devices, strengthening coordination, and optimizing information media to realize more effective, transparent, and accountable public services. Keywords: performance, village governance, public services, SOP, Sinarancang Village